DEVELOPING A SUPPLEMENTARY MATERIAL ON VOCABULARY DEVELOPMENT FOR YEAR-7 OF JUNIOR HIGH SCHOOL - Puspita, Agustina Ratna; ., Ikhsanudin; Sada, Clarry (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: This study aimed at developing a supplementary material on vocabulary development for Year-7 of Junior High School. With the assumption that they start their learning in this level, there is a need of vocabulary enrichment to supplement the textbook as vocabulary plays fundamental role in learning English for beginners. ADDIE (Analyze, Design, Develop, Implement, and Evaluate) approach was used as a guiding framework to develop the material. The analyses provide a basis on how the objectives and topics were formulated in the design phase. The building elements of the story were elaborated in the development phase and the implementation was done to see the applicability of the materials. Evaluation aims at assessing the standard qualities of the materials. In conclusion, this study has successfully developed a supplementary material under ADDIE framework. Â  Keywords: ADDIE, supplementary, pictorial dictionary Abstrak: Tujuan dari penelitian ini adalah untuk mengembangkan materi tambahan dalam peningkatan pembelajaran kosakata kelas 7 Sekolah Menengah Pertama. dengan asumsi bahwa siswa SMP kelas 7 mulai belajar Bahasa Inggris, maka perlu adanya buku tambahan untuk meningkatkan pengetahuan kosakata yang merupakan hal yang fundamental dalam pembelajaran bahasa. Kerangka pengembangan materi yang digunakan adalah ADDIE yang terdiri dari lima fase (Analyze, Design, Develop, Implement, and Evaluate). Fase pertama adalah analisis yang merupakan dasar pengembangan materi. Dalam fase desain, tujuan pembelajaran dan topik ditetapkan sesuai analisis. Elemen-elemen pembangun dari cerita yang terdapat dalam materi terelaborasi dalam fase pengembangan. Implementasi dari materi yang sudah dikembangkan dilakukan untuk mengetahui apakah materi bisa diterapkan dalam pembelajaran. Evaluasi bertujuan untuk menilai kualitas standard materi belajar. Sebagai kesimpulan, penelitian ini telah berhasil mengembangkan materi menggunakan kerangka ADDIE. Â  Kata Kunci: ADDIE, tambahan, kamus bergambar